Instructional Planning Modifications to Meet Social Distancing Requirements: Secondary and Post-Secondary Options - Trina Johnson Kilty; Andrea C. Burrows; Dane Christoffersen; Kevin Thomas Kilty; Kate Muir Welsh; Shawna McBride; Philip Bergmaier; Christian Bitzas; Cierra Rainey (MDPI AG, 2021)
Secondary and post-secondary science and engineering educators share common class arrangements with both a laboratory and lecture component, coordinating both components so they build upon each other to create meaningful learning experiences. The COVID-19 pandemic forced educators to convert lectures and exams to online delivery. Doing so came with trade-off decisions about sacrificing laboratory experience goals of hands-on practice, problem-solving, and learning concepts at a deeper, tactile level. Due to rapidly changing conditions, educators faced course redesign to accommodate social distancing and virtual learning requirements. In this study, a team of undergraduate college students including one secondary science preservice teacher planned a set of lessons for STEM outreach to a K-12 audience. The team faced challenges in planning meaningful learning experiences in the face of COVID-19 uncertainty. Options for secondary and post-secondary educators to consider are provided in this article.